A novel, low-cost and throughput selfing technique in sesame: A NOVEL, LOW-COST AND THROUGHPUT SELFING TECHNIQUE IN SESAME - K T RAMYA; N MUKTA; J JAWAHAR LAL; H H KUMARASWAMY; A R G RANGANTHA (Journal of Oilseeds Research, 2019)
Sesame (Sesamum indicum L.) is an oilseed crop, highly valued for its quality edible oil and direct confectionery uses. Though sesame is a self-pollinated crop, the opened flowers attract several groups of bees which promote cross pollination. Genetically pure seed obtained by ensuring self-pollination is an essential requirement for fixing the traits in genotypes, and for employing them in molecular and genomic studies. As of now, bagging technique is followed for selfing and this is not only tedious but also detrimental to the developing flowers. In order to overcome the limitations of the traditional selfing technique, a novel selfing technique has been developed using liquid glue, which is low cost, less labour intensive and high throughput method. This technique has no seasonal limitations and is applicable across any region where sesame is grown.